Carbon‐13 and carbon‐14 labeled dabigatran etexilate and tritium labeled dabigatran. (5th May 2016) - Latli, Bachir; Kiesling, Ralf; Aßfalg, Stefan; Chevliakov, Max; Hrapchak, Matt; Campbell, Scot; Gonnella, Nina; Busacca, Carl A.; Senanayake, Chris H.
Abstract : Dabigatran etexilate or pradaxa, a novel oral anticoagulant, is a reversible, competitive, direct thrombin inhibitor. It is used to prevent strokes in patients with atrial fibrillation and the formation of blood clots in the veins (deep venous thrombosis) in adults who have had an operation to replace a hip or a knee. Pradaxa is the only novel oral anticoagulant available with both proven superiority to warfarin and a specific reversal agent for use in rare emergency situations. The detailed description of the synthesis of carbon‐13 and carbon‐14 labeled dabigatran etexilate, and tritium labeled dabigatran is described. The synthesis of carbon‐13 dabigatran etexilate was accomplished in eight steps and in 6% overall yield starting from aniline‐ 13 C 6 . Ethyl bromoacetate‐1‐ 14 C was the reagent of choice in the synthesis of carbon‐14 labeled dabigatran etexilate in six steps and 17% overall yield. Tritium labeled dabigatran was prepared using either direct tritium incorporation under Crabtree's catalytic conditions or tritium‐dehalogenation of a diiodo‐precursor of dabigatran. Abstract : The detailed descriptions of the synthesis of carbon‐13 and carbon‐14 labeled dabigatran etexilate (pradaxa), and tritium labeled dabigatran are presented.